Recycling of textile wastes in fibre-cement composites - Monteiro, H. (2014)
Changing wastes into raw materials is one of the most favoured options for waste management, as it diverts wastes from landfill and saves resources. Fibres, either vegetable (cellulosic) or synthetic, may be added to cement pastes in order improve the properties of concrete or mortar by reinforcement. At the same time, if our source of fibres is wastes, then such processes make ways for recycling. In this work we studied the compatibility of residues from the nonwoven textile industry with Portland cement, with the aim of manufacturing fibre-cement composites. The temperature of cement setting was monitored and when fibre or other materials were added to cement pastes. The textile waste from needling machines investigated here is not compatible with cement. The reason is ascribed to a higher cotton content (65%), which enables cation exchange to occur in cement suspensions, and that disturbs cement setting reactions. On the other hand, however, synthetic fibres do not seem to hinder cement setting.